Itinararium Egerii na temat światła - Czyżewski, Bogdan Stanisław (Vox Patrum, 2019)
The Egeria, who have had pilgrimage to the Holy Land in 381-384, left us a significant testimony in the form of written diaries. Her itinerary is an exceptional work for scholars who are dedicated to work on history of monasticism, liturgy and customs prevailing in the Holy Land in the 4th century. Owing to this descriptions, we are able to look at the Jerusalem liturgy celebrated during the entire liturgical year including the precise localization of sacred places in the whole Holy Land, which she – tireless pilgrimage - decided to visit. In the Egeria’s Diaries we can read about the lights, which comes out of candles, candelabras, lamps and torches. One gets the impression that Egeria was trying to focus readers minds on three significant functions of the light in the liturgy. The light, which was lightning up during vespers, had been a thanksgiving prayer directed to God and had a spiritual character. The light accompanied pilgrims when they had been traveling from one temple to another, waiting for the services or just to light up the room where the liturgy was going to take place. Egeria the Pilgrimage wrote also about the light which was used to decorate the interiors and giving then splendor.